Profitability analysis of cigarette sub-sector companies with capital structure as an intervening variable - Bilqiis, Rifa Adila; Supriadi, Yudi Nur; Purwanto, Sri; Nurwati, Etty; Moeljadi, Moeljadi (Universitas Widya Mataram, 2025)
This study aims to examine and analyze the effects of liquidity and activity on profitability, with capital structure as an intervening variable. Liquidity and activity are proxied by the Current Ratio and Total Asset Turnover, respectively, while profitability is measured by Return on Assets, and capital structure is represented by the Debt to Equity Rasio. This study employs a quantitative research approach. The population consists of cigarette sub-sector companies that are officially registered and listed on the Indonesia Stock Exchange from 2018 to 2023. The study adopts a full sampling method, in which all members of the population serve as the research sample, comprising five cigarette sub-sector companies listed on the Indonesia Stock Exchange during the 2018–2023 period. Data analysis was conducted using the Panel Data Regression Model with the assistance of the EViews 12 software. The results of the study indicate that liquidity and capital structure have a negative effect on profitability, while activity has a positive effect on profitability. In addition, both liquidity and activity negatively affect capital structure as the intervening variable. Furthermore, capital structure is found to mediate the effects of liquidity and activity on profitability. The findings reveal that liquidity and capital structure have a significant negative effect on profitability, while activity has a significant positive effect, and capital structure effectively mediates the relationship between liquidity, activity, and profitability